Coherence Analysis of Sentinel-1A Images in Various Land Covers - Satrio Muhammad Alif; Ongky Anggara; Vidiya Ristiana (Jurnal Pendidikan Geografi Gea, 2023)
Coherence analysis is a valuable technique to assess the suitability and similarity of pixel pairs between two radar images taken at different times. In this study, we conducted coherence analysis on a series of Sentinel-1A images acquired between 2017 to 2022 in Palembang, Indonesia, encompassing various land covers. The analysis was conducted on different land covers, including urban areas, agricultural lands and natural terrains. The study aimed to identify land cover types with high coherence values Sentinel-1A images, as these could indicate stable or unchanged surfaces. The results show that land cover in Palembang which has high coherence is open land and built area. The average coherence value in the study area from 2017 to 2022 is ~0.2 to ~0.27, indicating relatively stable surfaces. This study is useful as initial consideration to utilize Sentinel-1A image for further research in earthquake and disaster analysis.